Perovskite semiconductor device and preparation method thereof
By introducing quantum doped layers and bismuth selenide electron selection layers into perovskite solar cells, the problems of perovskite solar cells in electron transmission and interface quality are solved, and the photoelectric conversion efficiency and battery performance are improved. It is suitable for Mass production.
Patent Information
- Application Number
- CN202411722784.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing perovskite solar cells have shortcomings in terms of energy level matching and carrier mobility of electron transport layer and hole transport layer, resulting in hindered electron transport, high recombination probability, low open circuit voltage and filling factor, and material humidity , oxygen and temperature sensitive affect battery performance.
Introduce quantum doped layers and bismuth selenide (Bi2Se3) electron selection layers to improve the structure of perovskite solar cells, improve light absorption capacity and carrier transmission efficiency through CdSe quantum dots and Bi2Se3 thin film materials, and optimize interface quality and energy level Matching, low-temperature preparation process is adopted.
It significantly improves the photoelectric conversion efficiency, short-circuit current density and fill factor of perovskite solar cells, reduces carrier recombination and heat loss, reduces process steps and energy consumption, and is suitable for large-scale production and commercial applications.
Smart Images

Figure CN119212411A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor devices, and in particular to a perovskite semiconductor device and a preparation method thereof. Background Art
[0002] Perovskite Solar Cells (PSCs) have become a research hotspot in the photovoltaic field in recent years due to their high photoelectric conversion efficiency, low cost and easy preparation. The typical perovskite semiconductor device structure includes a transparent conductive oxide layer, an electron transport layer, a perovskite light absorption layer, a hole transport layer and a metal electrode.
[0003] Current perovskite solar cells still face some challenges in practical applications. The electron transport layer (such as TiO 2 ) and hole transport layers (such as Spiro-OMeTAD) have deficiencies in energy level matching and carrier mobility, such as TiO 2 It requires high-temperature sintering, has a complex process, and has a relatively low electron mobility, which hinders the rapid transmission of electrons and limits the effective separation and transmission of carriers; there are defects at the interface between the perovskite layer and the adjacent functional layer, and the energy level matching between the functional layers is not ideal, which leads to the obstruction of carrier transmission at the interface, increases the recombination probability, and reduces the open circuit voltage and fill factor of the battery; the perovskite material has insufficient absorption capacity for some visible light and near-infrared light, which limits the comprehensive utilization of solar energy; the perovskite material is sensitive to environmental factors such as humidity, oxygen and temperature, which causes the battery performance to decay over time, affecting practical applications.
[0004] Therefore, continuously improving the structure of existing perovskite solar cells to overcome the above-mentioned defects is the current development direction of perovskite solar cell technology. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a perovskite semiconductor device and a preparation method thereof, by improving the structure of the perovskite solar cell, introducing a quantum dot doping layer and bismuth selenide (Bi 2 Se 3 ) electron selective layer, which significantly improves the performance of the battery.
[0006] The present invention adopts the following technical solutions: A perovskite semiconductor device adopts a transparent glass substrate. The structure of the perovskite semiconductor device is as follows from the transparent glass substrate: a first transparent conductive oxide layer, a perovskite layer, a quantum dot doping layer, an electron selection layer, an electron transport layer, a buffer layer, and a second transparent conductive oxide layer.
[0007] Furthermore, the first transparent conductive oxide layer and the second transparent conductive oxide layer are both made of ITO; the perovskite layer is made of CH 3 NH 3 PbI 3 The quantum dot doping layer is doped with CdSe quantum dots; the electron selection layer is doped with Bi 2 Se 3 Thin film materials.
[0008] Furthermore, the electron transport layer is TiO 2 The film has a thickness of 10-20 nanometers; the buffer layer is SnO 2 Thin film, thickness is 10-20 nanometers.
[0009] Furthermore, the Bi 2 Se 3 The thickness of the film is 20-50 nanometers.
[0010] Furthermore, the particle size of the CdSe quantum dots in the quantum dot doping layer is in the range of 2-5 nanometers, and the thickness is in the range of 5-10 nanometers.
[0011] Furthermore, the thickness of the first transparent conductive oxide layer and the second transparent conductive oxide layer are both 100-200 nanometers.
[0012] Furthermore, the thickness of the perovskite layer is 300-800 nanometers.
[0013] Furthermore, the semiconductor device also includes a top electrode, and the top electrode is one of gold, silver, copper, aluminum metals, or a conductive carbon material.
[0014] Furthermore, the semiconductor device further comprises: coating a layer of SiO with a thickness of 50-100 nanometers on the surface of the glass substrate. 2 Anti-reflective coating to reduce light reflection losses.
[0015] A method for preparing a perovskite semiconductor device, the method comprising the following steps: a) Substrate treatment: provide a transparent glass substrate, ultrasonically clean it in acetone, ethanol and deionized water in sequence, each time for 5 minutes, and dry it at 80°C.
[0016] b) Deposition of the first transparent conductive oxide layer: an ITO layer was deposited on a glass substrate by radio frequency magnetron sputtering with a sputtering power of 50 W and an argon gas flow rate of 50 sccm for 20-30 minutes at room temperature.
[0017] c) Deposition of perovskite layer: CH4O2 was spin-coated on the ITO layer at a speed of 3000 rpm. 3 NH 3 PbI3 Solution, spin coating time 20-30 seconds, deposited CH with a thickness of 300-800 nm 3 NH 3 PbI 3 The solution was then annealed at 100 °C for 10 min.
[0018] d) Formation of quantum dot doping layer: Spin coating the CdSe quantum dot solution on the surface of the perovskite layer at a speed of 2000 rpm for 2-10 seconds, and annealing at 100° C. for 20 minutes to form a uniform CdSe quantum dot doping layer.
[0019] e) Deposition of the electron selective layer: Bi is deposited on the quantum dot doped layer by vacuum thermal evaporation. 2 Se 3 layer, evaporation rate 0.1nm / s, vacuum degree 5×10 -4 Pa.
[0020] f) Deposition of electron transport layer: on Bi 2 Se 3 TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen is used as a carrier gas, the reaction temperature is 400°C, and the time is 10-30 minutes.
[0021] g) Deposition of buffer layer: On TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen is used as a carrier gas, the reaction temperature is 350°C, and the time is 10-20 minutes.
[0022] h) Deposition of the second transparent conductive oxide layer: On SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 20-30 minutes at room temperature to complete the preparation of the battery.
[0023] Furthermore, CdSe quantum dots with a particle size of 2-10 nanometers are dispersed in a solvent to form a quantum dot solution, wherein the solvent is toluene, and the concentration of CdSe in the quantum dot solution is 10 mg / mL.
[0024] Compared with the prior art, the present invention has the following beneficial effects: Compared with existing perovskite semiconductor devices, the perovskite semiconductor device provided by the present invention has higher short-circuit current and energy conversion efficiency. The introduction of quantum dot doping layer and bismuth selenide layer synergistically improves the light absorption capacity and carrier transmission efficiency of the battery, significantly improving the photoelectric conversion efficiency; improved interface quality and optimized energy level matching reduce carrier recombination and heat loss, and the key performance indicators of the battery such as open circuit voltage, short-circuit current density, and fill factor are all improved. In addition, the battery preparation process of the present invention adopts a low-temperature preparation method, which reduces process steps and energy consumption, reduces production costs, and is conducive to large-scale production and commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of a perovskite semiconductor device of the present invention.
[0026] Figure numerals: 1 - transparent glass substrate, 2 - first transparent conductive oxide layer, 3 - perovskite layer, 4 - quantum dot doping layer, 5 - electron selective layer, 6 - electron transport layer, 7 - buffer layer, 8 - second transparent conductive oxide layer. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that CdSe quantum dots have a size-adjustable band structure. By controlling the particle size of quantum dots (2-5 nanometers), its absorption spectrum can be adjusted. The quantum dot doping layer can absorb high-energy photons (short-wavelength region) that the perovskite layer has not fully utilized, thereby achieving more comprehensive utilization of the solar spectrum and increasing the generation of photogenerated carriers. The quantum dots fill the defects and gaps on the surface of the perovskite layer, smooth the interface, reduce the interface state density, reduce the probability of carrier recombination at the interface, and improve the separation and transmission efficiency of carriers. A favorable energy level gradient is formed between the CdSe quantum dots and the perovskite layer, which accelerates the transmission of electrons to the electron selective layer, improves the mobility of photogenerated electrons, and helps to increase the short-circuit current density of the battery.
[0029] Bi 2 Se 3 It is a topological insulator with high electron mobility and good conductivity. As an electron selective layer, Bi 2 Se 3 It can effectively and selectively transmit electrons, block holes, and reduce carrier recombination losses.2 Se 3 The energy level structure of the perovskite layer and the electron transport layer (TiO 2 ) have a good match between them, which helps to reduce the energy barrier at the interface and promote the smooth transmission of electrons; at the same time, Bi 2 Se 3 The thin film can be prepared by vacuum thermal evaporation at a relatively low temperature, avoiding the damage of high-temperature processes to the perovskite material. It is suitable for temperature-sensitive applications such as flexible substrates, expanding the application range of the battery.
[0030] like Figure 1 As shown, it is a schematic diagram of the structure of a perovskite semiconductor device of the present invention, wherein the semiconductor device adopts a transparent glass substrate 1, and the structure of the perovskite semiconductor device is, from the transparent glass substrate 1 to the top, a first transparent conductive oxide layer 2, a perovskite layer 3, a quantum dot doping layer 4, an electron selection layer 5, an electron transport layer 6, a buffer layer 7, and a second transparent conductive oxide layer 8.
[0031] The first transparent conductive oxide layer 2 and the second transparent conductive oxide layer 8 are both made of ITO; the perovskite layer 3 is made of CH 3 NH 3 PbI 3 The quantum dot doping layer 4 is doped with CdSe quantum dots; the electron selection layer 5 is doped with Bi 2 Se 3 Thin film material. The electron transport layer 5 is TiO 2 The film has a thickness of 10-20 nanometers; the buffer layer 6 is SnO 2 The film has a thickness of 10-20 nanometers. 2 Se 3 The thickness of the film is 20-50 nanometers. The particle size of the CdSe quantum dots in the quantum dot doping layer is in the range of 2-5 nanometers and the thickness is 5-10 nanometers. The thickness of the first transparent conductive oxide layer and the second transparent conductive oxide layer are both 100-200 nanometers. The thickness of the perovskite layer is 300-800 nanometers. The semiconductor device also includes a top electrode, which is one of gold, silver, copper, aluminum metals, or a conductive carbon material. The semiconductor device also includes: coating a layer of SiO with a thickness of 50-100 nanometers on the surface of the glass substrate. 2 Anti-reflection coating to reduce light reflection loss. In order to further quantify the key performance indicators of the battery of the present invention, such as open circuit voltage, short circuit current density, fill factor, etc., the following examples and comparative examples are provided, prepared according to different process conditions, and various parameters of the final battery are measured.
[0032] Example 1 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 20 minutes to obtain an ITO layer with a thickness of 100 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH 3 PbI 3 The solution was spin-coated for 20 seconds to deposit a CH layer with a thickness of 300 nm. 3 NH 3 PbI 3 The solution was then annealed at 100°C for 10 minutes; the CdSe quantum dot solution was applied to the surface of the perovskite layer by spin coating at a speed of 2000 rpm for 2 seconds, and annealed at 100°C for 20 minutes to form a 5-nanometer-thick uniform CdSe quantum dot doping layer; Bi was deposited on the quantum dot doping layer by vacuum thermal evaporation. 2 Se 3 layer, evaporation rate 0.1nm / s, vacuum degree 5×10 -4 Pa, evaporation 200 seconds; in Bi 2 Se 3 TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 10 minutes; in TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 10 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 20 minutes at room temperature to complete the preparation of the battery.
[0033] The semiconductor device prepared by the above method has an open circuit voltage of 0.6V and a short circuit current of 34.9mA / cm 2 , the filling factor is 0.76 and the photoelectric conversion efficiency is 16.9%.
[0034] Example 2 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 30 minutes to obtain an ITO layer with a thickness of 200 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH 3 PbI 3 The solution was spin-coated for 30 seconds to deposit a CH layer with a thickness of 800 nm. 3 NH 3 PbI 3 The solution was then annealed at 100°C for 10 minutes; the CdSe quantum dot solution was applied to the surface of the perovskite layer by spin coating at a speed of 2000 rpm for 10 seconds, and annealed at 100°C for 20 minutes to form a 10-nanometer-thick uniform CdSe quantum dot doping layer; Bi was deposited on the quantum dot doping layer by vacuum thermal evaporation 2 Se 3 layer, evaporation rate 0.1nm / s, vacuum degree 5×10 -4 Pa, evaporation 500 seconds; in Bi 2 Se 3 TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 30 minutes; in TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 20 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 30 minutes at room temperature to complete the preparation of the battery.
[0035] The open circuit voltage of the semiconductor device prepared by the above method is 0.58V and the short circuit current is 33.3mA / cm 2 , the filling factor is 0.75 and the photoelectric conversion efficiency is 16.8%.
[0036] Example 3 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 25 minutes to obtain an ITO layer with a thickness of 160 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH 3 PbI 3 The solution was spin-coated for 26 seconds to deposit a 500 nm thick CH 3 NH 3 PbI 3 The solution was then annealed at 100°C for 10 minutes; the CdSe quantum dot solution was applied to the surface of the perovskite layer by spin coating at a speed of 2000 rpm for 6 seconds, and annealed at 100°C for 20 minutes to form a 7-nanometer-thick uniform CdSe quantum dot doping layer; Bi was deposited on the quantum dot doping layer by vacuum thermal evaporation. 2 Se 3 layer, evaporation rate 0.1nm / s, vacuum degree 5×10 -4 Pa, evaporation 350 seconds; in Bi 2 Se 3 TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 20 minutes; in TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 15 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 25 minutes at room temperature to complete the preparation of the battery.
[0037] The semiconductor device prepared by the above method has an open circuit voltage of 0.62V and a short circuit current of 34.9mA / cm 2 , the filling factor is 0.77 and the photoelectric conversion efficiency is 16.9%.
[0038] In order to further verify that the synergistic effect of the quantum dot doping layer and the bismuth selenide layer improves the light absorption capacity and carrier transfer efficiency of the battery, the following comparative examples are provided: Comparative Example 1 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 25 minutes to obtain an ITO layer with a thickness of 160 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH 3 PbI 3 The solution was spin-coated for 26 seconds to deposit a 500 nm thick CH 3 NH 3 PbI 3 solution, followed by annealing at 100 °C for 10 min; Bi deposited by vacuum thermal evaporation 2 Se 3 layer, evaporation rate 0.1nm / s, vacuum degree 5×10 -4 Pa, evaporation 350 seconds; in Bi 2 Se 3 TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 20 minutes; in TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 15 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 25 minutes at room temperature to complete the preparation of the battery.
[0039] The semiconductor device prepared by the above method has an open circuit voltage of 0.57V and a short circuit current of 30.5mA / cm 2 , the filling factor is 0.72 and the photoelectric conversion efficiency is 15.8%.
[0040] Comparative Example 2 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 25 minutes to obtain an ITO layer with a thickness of 160 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH3 PbI 3 The solution was spin-coated for 26 seconds to deposit a 500 nm thick CH 3 NH 3 PbI 3 The solution was then annealed at 100°C for 10 minutes; the CdSe quantum dot solution was applied to the surface of the perovskite layer by spin coating at 2000 rpm for 6 seconds, and annealed at 100°C for 20 minutes to form a 7-nanometer-thick uniform CdSe quantum dot doping layer; TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 20 minutes; in TiO 2 SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 15 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 25 minutes at room temperature to complete the preparation of the battery.
[0041] The open circuit voltage of the semiconductor device prepared by the above method is 0.56V and the short circuit current is 31.2mA / cm 2 , the filling factor is 0.73 and the photoelectric conversion efficiency is 15.4%.
[0042] Comparative Example 3 The semiconductor device of this embodiment is prepared using the following process conditions and preparation method: A transparent glass substrate is provided, and ultrasonically cleaned in acetone, ethanol and deionized water in sequence for 5 minutes each time, and dried at 80°C; a first transparent conductive oxide layer is deposited: an ITO layer is deposited on the glass substrate by a radio frequency magnetron sputtering method, with a sputtering power of 50W and an argon gas flow rate of 50sccm, and the deposition is carried out at room temperature for 25 minutes to obtain an ITO layer with a thickness of 160 nanometers; CH is spin-coated on the ITO layer by a spin coating method at a speed of 3000rpm; 3 NH 3 PbI 3 The solution was spin-coated for 26 seconds to deposit a 500 nm thick CH 3 NH 3 PbI 3 solution, followed by annealing at 100 °C for 10 min; TiO deposited by CVD 2 Thin film, using titanium tetrachloride TiCl 4 As a precursor, oxygen was used as a carrier gas, the reaction temperature was 400 ° C, and the time was 20 minutes; in TiO 2SnO deposited by CVD on the 2 layer, using tin tetrachloride SnCl 4 As a precursor, oxygen as a carrier gas, reaction temperature 350 ° C, time 15 minutes; in SnO 2 The ITO layer is deposited on the layer by radio frequency magnetron sputtering, with a sputtering power of 50 W, an argon gas flow rate of 50 sccm, and deposition for 25 minutes at room temperature to complete the preparation of the battery.
[0043] The semiconductor device prepared by the above method has an open circuit voltage of 0.54V and a short circuit current of 29.8mA / cm 2 , the filling factor is 0.67 and the photoelectric conversion efficiency is 14.8%.
[0044] It should be noted that the Voc of Examples 1-3 are 0.6 V, 0.58 V and 0.62 V, respectively, which are higher than the Voc of Comparative Examples 1-3 (0.57 V, 0.56 V and 0.54 V); the Jsc of Examples 1-3 are 34.9 mA / cm 2 、33.3mA / cm 2 and 34.9mA / cm 2 , which are higher than the Jsc of Comparative Examples 1-3 (30.5mA / cm², 31.2mA / cm² and 29.8mA / cm²); the FF of Examples 1-3 are 0.76, 0.75 and 0.77, respectively, which are higher than the FF of Comparative Examples 1-3 (0.72, 0.73 and 0.67); the PCE of Examples 1-3 are 16.9%, 16.8% and 16.9%, respectively, which are higher than the PCE of Comparative Examples 1-3 (15.8%, 15.4% and 14.8%).
[0045] The introduction of quantum dot doping layer and bismuth selenide layer not only improves the photoelectric conversion efficiency, but also significantly improves the open circuit voltage, short circuit current and fill factor; the different thicknesses of each layer of materials have a certain impact on the performance of semiconductor devices, but in general, the CdSe quantum dot doping layer and Bi 2 Se 3 The structure of the layers can maintain a high photoelectric conversion efficiency.
[0046] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A perovskite semiconductor device, wherein the semiconductor device uses a transparent glass substrate, characterized in that: The structure of the perovskite semiconductor device is, from the transparent glass substrate upward, a first transparent conductive oxide layer, a perovskite layer, a quantum dot doping layer, an electron selection layer, an electron transport layer, a buffer layer, and a second transparent conductive oxide layer; The first transparent conductive oxide layer and the second transparent conductive oxide layer are both made of ITO; the perovskite layer is made of CH3NH3PbI3, the quantum dot doping layer is doped with CdSe quantum dots; and the electron selection layer is made of Bi2Se3 thin film material.
2. A perovskite semiconductor device according to claim 1, characterized in that: The electron transport layer is a TiO2 film with a thickness of 10-20 nanometers; the buffer layer is a SnO2 film with a thickness of 10-20 nanometers.
3. A perovskite semiconductor device according to claim 2, characterized in that: The thickness of the Bi2Se3 film is 20-50 nanometers.
4. The perovskite semiconductor device according to claim 1, wherein: The particle size of the CdSe quantum dots in the quantum dot doping layer is in the range of 2-5 nanometers, and the thickness is in the range of 5-10 nanometers.
5. The perovskite semiconductor device according to claim 1, wherein: The thickness of the first transparent conductive oxide layer and the second transparent conductive oxide layer are both 100-200 nanometers.
6. The perovskite semiconductor device according to claim 1, wherein: The thickness of the perovskite layer is 300-800 nanometers.
7. A method for preparing a perovskite semiconductor device according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: a) Substrate treatment: providing a transparent glass substrate, ultrasonically cleaning it in acetone, ethanol and deionized water in sequence, each for 5 minutes, and drying it at 80°C; b) Deposition of the first transparent conductive oxide layer: Depositing an ITO layer on a glass substrate by radio frequency magnetron sputtering, with a sputtering power of 50 W and an argon gas flow rate of 50 sccm for 20-30 minutes at room temperature; c) Deposition of the perovskite layer: Spin coating a CH3NH3PbI3 solution on the ITO layer at a speed of 3000 rpm for 20-30 seconds to deposit a CH3NH3PbI3 solution with a thickness of 300-800 nm, followed by annealing at 100°C for 10 minutes; d) Formation of quantum dot doping layer: Spin coating at 2000 rpm for 2-10 seconds to coat the CdSe quantum dot solution on the surface of the perovskite layer, and annealing at 100° C. for 20 minutes to form a uniform CdSe quantum dot doping layer; e) Deposition of the electron selective layer: A Bi2Se3 layer was deposited on the quantum dot doped layer by vacuum thermal evaporation with an evaporation rate of 0.1 nm / s and a vacuum degree of 5×10 -4 Pa; f) Deposition of electron transport layer: TiO2 thin film deposited on Bi2Se3 layer by CVD method, using titanium tetrachloride TiCl4 as precursor, oxygen as carrier gas, reaction temperature 400°C, time 10-30 minutes; g) Deposition of buffer layer: SnO2 layer deposited on TiO2 layer by CVD method, using tin tetrachloride SnCl4 as precursor, oxygen as carrier gas, reaction temperature 350°C, time 10-20 minutes; h) Deposition of the second transparent conductive oxide layer: An ITO layer is deposited on the SnO2 layer by radio frequency magnetron sputtering, with a sputtering power of 50 W and an argon gas flow rate of 50 sccm. The deposition time is 20-30 minutes at room temperature to complete the preparation of the battery.
8. The preparation method according to claim 7, characterized in that: The CdSe quantum dot solution is prepared by dispersing CdSe quantum dots with a particle size of 2-10 nanometers in a solvent to form a quantum dot solution, wherein the solvent is toluene and the concentration of CdSe in the quantum dot solution is 10 mg / mL.
Citation Information
Patent Citations
Perovskite solar battery based on CdSe nanocrystals and preparation method
CN104167453A
Perovskite solar energy cell utilizing topology insulator as electron transmission layer
CN107093670A